Utilization of Social Media to Support Digital Marketing in Village Communities and Village MSMEs - Lala Hucadinota Ainul Amri; Muhammad Taali; Fredy Susanto; Allya Rahmanda Adhatul Jana; Rusmadiah Anwar (SWAGATI : Journal of Community Service, 2026)
Utilizing social media is crucial in supporting digital marketing for Community Groups (Pokmas) and Micro, Small, and Medium Enterprises (MSMEs) during digital transformation. This community service activity aims to improve MSMEs' and Pokmas members' ability to use social media as a marketing tool for local products in Hargosari Village, Sine District, Ngawi Regency. The methods included outreach, training, mentoring, and evaluation through interviews, observations, and focus group discussions. Activity results showed that using Instagram, Facebook, and WhatsApp improved participants' knowledge and skills in digital marketing. Market reach expanded and interaction with consumers increased. Participants also became more able to create engaging and informative promotional content. Challenges included limited digital literacy and suboptimal marketing feature use. Through this activity, MSMEs and Pokmas gained understanding and practical skills in using social media for digital marketing. Therefore, ongoing mentoring is needed to ensure the sustainability and optimization of social media utilization in supporting the competitiveness of MSMEs in rural areas.